2003
DOI: 10.1093/ajcn/77.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic de novo lipogenesis in normoinsulinemic and hyperinsulinemic subjects consuming high-fat, low-carbohydrate and low-fat, high-carbohydrate isoenergetic diets

Abstract: These results support the concept that both hyperinsulinemia and a low-fat diet increase DNL, and that DNL contributes to hypertriglyceridemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
270
1
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 425 publications
(299 citation statements)
references
References 35 publications
15
270
1
5
Order By: Relevance
“…2) were identified whose expression was changed in the livers of HCD-fed animals. These genes include the ones that encode the enzymes, approximately 20, involved in glucose and fructose metabolism and their conversion to fat [10,12,15] ( Table 3 and Table I of supplementary material, and Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) were identified whose expression was changed in the livers of HCD-fed animals. These genes include the ones that encode the enzymes, approximately 20, involved in glucose and fructose metabolism and their conversion to fat [10,12,15] ( Table 3 and Table I of supplementary material, and Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…Human clinical investigations have demonstrated that a diet low in fat and rich in carbohydrates (closely resembling the HCD used in our mouse study), even when administered for short periods of time, for example, 5 or 25 days, can lead to occurrence of uncomplicated fatty liver [12][13][14][15]. Thus, this mouse model is a highly relevant means of investigating mechanisms of hepatic steatosis.…”
Section: Introductionmentioning
confidence: 91%
“…31 The major confounding factor seems to be the degree of insulin resistance. 32 The key issue is whether or not obesity (at least some form of obesity) may be associated to an increase in DNL through the regular consumption of high CHO meals in state of positive energy balance.…”
Section: Do Obese Women Convert More Cho To Fat Than Lean Women?mentioning
confidence: 99%
“…Previous studies (31) have indicated that serum lipids could reach a new steady state after 5 days of dietary intervention. Therefore, a regime of 7 days of washout control diet followed by 6 days of high-CHO intervention diet was adopted in this study.…”
Section: Subjects and Dietsmentioning
confidence: 95%